Coupling CO2 electrolysis and downstream processing via heat pump-based waste heat recovery - Dal Mas, Riccardo; Carta, Andrea; Somoza-Tornos, Ana; Kiss, Anton A. (Computers & chemical engineering, 2026)
•Heat pumps can be used to upgrade the waste heat and drive the fluid separations.•CO2 emissions for the process with dilute streams are reduced by 29–84 % with a heat pump.•Heat pump COP increases by 32–44 % with electrolyzer operating at 70 °C from 50 °C base case.•Effective system performance operating with 40 % cell efficiency and heat integration. The electrification of chemical processes and CO2 utilization are key approaches to improving efficiency and reducing CO2 emissions in the process industry. The development of electrolyzers has gathered momentum, enabling the potential introduction of renewable electrons into the manufacture of CO2-based chemicals. While the performance of electrolyzers is subject to improvements driven by the experimental community, the generation of waste heat is unavoidable due to electrical resistances and process inefficiencies within the electrochemical cells. Nonetheless, reusing this waste heat has yet to be investigated for CO2 electrolyzers. This novel work shows the potential for upgrading the electrolyzer waste heat by means of a heat pump, enabling its utilization in the separation processes downstream of the carbon dioxide electrolyzer. The product chosen is formic acid (60 kt/y), and for our system, the waste heat represents approximately 60 % of the power input to the electrochemical cells, and it can be upgraded from 50 °C to 120 °C to drive the azeotropic distillation of formic acid and water. This integration results in the electrification of 76 % of the separation energy duty, yielding a decrease in CO2 emissions of 29–84 % compared to the conventional production, depending on the source of electricity. The results demonstrate that the use of traditional heating media in thermal separation processes can be offset and substituted with (renewable) electrical energy, allowing for an increased overall system efficiency. This approach can be readily extended to different productions based on carbon dioxide electroreduction, for example for methanol and ethanol manufacture. This eco-efficient process design leads to a deeper penetration of renewable energy into chemical manufacturing, as both reaction and separation are driven by electricity.